An antibacterial and aging-resistant shopping bag and a preparation method and application thereof

CN122978664APending Publication Date: 2026-10-27ANHUI YINGKE NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611365961.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-04
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]有鉴于此,本申请提供一种抗菌耐老化购物袋及其制备方法和应用,该抗菌耐老化购物袋具有良好的抗菌性能、耐老化性能和力学性能,解决了现有可降解购物袋抗菌性能差、耐老化性能不足、组分相容性差及综合性能难以兼顾的问题,产品兼具良好抗菌性能、耐老化性能与力学性能,制备工艺可控,适合规模化生产

Benefits of technology

[0050]本申请提供的抗菌耐老化购物袋通过环氧官能化PBAT树脂、复合抗菌剂和耐老化母粒的协同作用,实现了抗菌性能、耐老化性能和力学性能的统一。相较于现有技术,该抗菌耐老化购物袋具有抗菌性能优异、耐老化性能好、力学性能稳定及加工性能良好等特点,同时制备工艺简单、各原料均为常规市售产品,具备良好的可实施性和产业化应用前景。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses an antibacterial and aging-resistant shopping bag and a preparation method and application thereof, and relates to the technical field of packaging materials. The antibacterial and aging-resistant shopping bag provided by the application realizes the unity of antibacterial performance, aging resistance and mechanical properties, and the unity of use performance and environmental protection performance, solves the common problems in the industry, such as poor antibacterial performance, insufficient aging resistance, poor component compatibility and difficult comprehensive performance, and the product has excellent antibacterial performance, good aging resistance, stable mechanical properties, good processing performance and controllable preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of packaging materials technology, and in particular to an antibacterial and aging-resistant shopping bag, its preparation method, and its application. Background Technology

[0002] Shopping bags are among the most frequently used packaging materials in daily life. Traditional shopping bags are mainly made of polyolefin resins such as polyethylene and polypropylene. Although they have advantages such as good mechanical properties and low cost, they are extremely difficult to degrade after disposal, and long-term accumulation can cause serious environmental pollution. In recent years, biodegradable shopping bags made from biodegradable resins such as poly(butylene adipate / terephthalate) copolymer, polylactic acid, and polybutylene succinate have gradually gained attention. However, while the ester bonds in the molecular structure of these biodegradable resins endow them with biodegradability, they also generally result in poor aging resistance. Under the influence of environmental factors such as light, heat, and oxygen, molecular chains are prone to breakage, leading to problems such as yellowing, brittleness, and decreased mechanical strength, making it difficult to meet the durability requirements of shopping bags during actual storage and use.

[0003] Furthermore, shopping bags, used in packaging for food, daily necessities, and fresh produce, often come into contact with various items, making them prone to bacterial growth. Therefore, their antibacterial properties are crucial. Currently, to improve the antibacterial performance of shopping bags, silver-based or zinc-based inorganic antibacterial agents, or organic antibacterial agents such as chitosan, are commonly added directly. However, inorganic antibacterial agents, when added directly, are prone to aggregation due to their small particle size and large specific surface area, resulting in uneven dispersion within the resin matrix and unstable antibacterial effects. Organic antibacterial agents, on the other hand, suffer from poor temperature resistance and are prone to migration and precipitation, leading to a significant decline in antibacterial performance after long-term use.

[0004] Meanwhile, to improve the aging resistance of biodegradable resins, existing technologies often add additives such as antioxidants, light stabilizers, or ultraviolet absorbers. However, single additives or simple compound systems often fail to simultaneously meet the protection requirements for both thermo-oxidative and photo-oxidative aging, resulting in insufficient performance retention of the film under comprehensive aging conditions. Furthermore, when multiple biodegradable resins are used or when biodegradable resins are blended with fillers, the poor compatibility and weak interfacial bonding between different components easily lead to deterioration of mechanical properties and processing difficulties.

[0005] To address the aforementioned technical shortcomings, there is an urgent need to improve existing technologies. Summary of the Invention

[0006] In view of this, this application provides an antibacterial and aging-resistant shopping bag, its preparation method and application. The antibacterial and aging-resistant shopping bag has good antibacterial properties, aging resistance and mechanical properties, which solves the problems of poor antibacterial properties, insufficient aging resistance, poor component compatibility and difficulty in achieving comprehensive performance of existing biodegradable shopping bags. The product has good antibacterial properties, aging resistance and mechanical properties, and the preparation process is controllable and suitable for large-scale production.

[0007] In the first aspect, this application provides an antibacterial and aging-resistant shopping bag, the technical solution of which is as follows:

[0008] An antibacterial and aging-resistant shopping bag, by weight, comprises the following raw materials: 80-95 parts of matrix resin, 5-20 parts of epoxy-functionalized PBAT resin, 0.5-5 parts of composite antibacterial agent, 1-10 parts of aging-resistant masterbatch, 0.5-5 parts of compatibilizer and 0.1-1 parts of lubricant;

[0009] The matrix resin is selected from one or more of PBAT, polylactic acid, polyethylene, or polypropylene;

[0010] The compatibilizer is selected from one or more of the following: ethylene-acrylate copolymer, ethylene-vinyl acetate copolymer, ethylene-glycidyl methacrylate copolymer, and styrene-maleic anhydride copolymer.

[0011] The lubricant is selected from one or more of zinc stearate, calcium stearate, oleamide, or erucamide.

[0012] Optionally, the preparation method of the epoxy-functionalized PBAT resin includes the following steps:

[0013] Adipic acid, terephthalic acid, 1,4-butanediol, tetrabutyl titanate and modified monomers are mixed and then subjected to esterification and polycondensation reactions in sequence. The mixture is then discharged, cooled and granulated to obtain modified poly(adipic acid / butylene terephthalate) copolymer.

[0014] The modified poly(adipate) / butylene terephthalate copolymer, epoxy chain extender and antioxidant are mixed and then subjected to melt reaction extrusion, followed by granulation to obtain the epoxy-functionalized PBAT resin.

[0015] Optionally, the mass-to-volume ratio of adipic acid, terephthalic acid, 1,4-butanediol, tetrabutyl titanate, and the modified monomer is 1 g : (1.0~1.4) g : (0.7~1.05) mL : (0.0005~0.005) mL : (0.001~0.01) g, and the modified monomer is selected from one or more of trimellitic anhydride, pyromellitic anhydride, glycerol, or pentaerythritol.

[0016] Optionally, the esterification reaction is carried out under nitrogen protection, at a temperature of 160~220℃, for a time of 2~5h.

[0017] Optionally, the polycondensation reaction is carried out at a temperature of 240-270°C, a vacuum degree of 10-100 Pa, and a time of 2-6 hours.

[0018] Optionally, the mass ratio of the modified poly(adipate) / butylene terephthalate copolymer, the epoxy chain extender, and the antioxidant is 1:0.005~0.03:0.001~0.005, and the epoxy chain extender is selected from one or both of ADR 4368 or ADR 4370S.

[0019] Optionally, the melt reactive extrusion is carried out in a twin-screw extruder, and the temperature of the melt reactive extrusion is 160~190℃, and the screw speed is 200~300r / min.

[0020] Optionally, the preparation method of the composite antibacterial agent includes the following steps:

[0021] Chitosan, isopropanol aqueous solution and glycidyltrimethylammonium chloride were mixed and subjected to quaternization reaction, then filtered, washed and dried to obtain chitosan quaternary ammonium salt;

[0022] Nano zinc oxide, water, silver nitrate aqueous solution and reducing agent are mixed and a reduction reaction is carried out to obtain silver-loaded nano zinc oxide dispersion;

[0023] The silver-loaded zinc oxide nano-dispersion, chitosan quaternary ammonium salt, and γ-aminopropyltriethoxysilane were mixed and modified, then filtered, washed, dried, and ground to obtain the composite antibacterial agent.

[0024] Optionally, the mass-to-volume ratio of chitosan, isopropanol aqueous solution, and glycidyltrimethylammonium chloride is 1 g: (10~30) mL: (0.5~2) g, and the volume concentration of the isopropanol aqueous solution is 50%~80%.

[0025] Optionally, the quaternization reaction is carried out at a temperature of 60-80°C for a time of 6-12 hours.

[0026] Optionally, the temperature of the first drying is 60~80℃ and the time is 8~12h.

[0027] Optionally, the mass-volume ratio of the nano zinc oxide, water, silver nitrate aqueous solution and reducing agent is 1g:(15~30)mL:(1~5)mL:(0.1~1)g, the mass concentration of the silver nitrate aqueous solution is 1%~5%, and the reducing agent is selected from one or more of sodium citrate, glucose or ascorbic acid.

[0028] Optionally, the reduction reaction is carried out at a temperature of 50-80°C for a time of 1-3 hours.

[0029] Optionally, the mass-to-volume ratio of the silver-loaded zinc oxide nano-dispersion, chitosan quaternary ammonium salt, and γ-aminopropyltriethoxysilane is 1 mL: (0.02~0.1) g: (0.002~0.02) mL.

[0030] Optionally, the modification treatment is performed at a temperature of 50-70°C for 2-4 hours.

[0031] Optionally, the second drying temperature is 60~100℃ and the time is 4~12h.

[0032] Optionally, the particle size of the ground product is ≤500nm.

[0033] Optionally, the method for preparing the aging-resistant masterbatch includes the following steps:

[0034] The carrier resin, antioxidant 1010, antioxidant 168, hindered amine light stabilizer 622, ultraviolet absorber UV-326 and polyethylene wax are mixed and stirred to obtain a premix.

[0035] The premixed material is melt-mixed and extruded, and then granulated to obtain the aging-resistant masterbatch.

[0036] Optionally, the carrier resin is selected from one or both of low-density polyethylene and linear low-density polyethylene.

[0037] Optionally, the mass ratio of the carrier resin, antioxidant 1010, antioxidant 168, hindered amine light stabilizer 622, ultraviolet absorber UV-326 and polyethylene wax is 1:0.05~0.15:0.05~0.15:0.05~0.15:0.05~0.15:0.02~0.05.

[0038] Optionally, the stirring speed is 500~1500 r / min, the temperature is 25~50℃, and the time is 10~30 min.

[0039] Optionally, the melt-mixing extrusion is carried out in a twin-screw extruder at a temperature of 150~180℃ and a screw speed of 100~300 r / min.

[0040] Secondly, this application provides a method for preparing the antibacterial and aging-resistant shopping bag described in the aforementioned scheme, comprising the following steps:

[0041] The matrix resin, epoxy-functionalized PBAT resin, composite antibacterial agent, aging-resistant masterbatch, compatibilizer and lubricant are mixed and then subjected to a mixing treatment to obtain a mixture.

[0042] The mixture is melt-extruded and granulated to obtain antibacterial and aging-resistant granules.

[0043] The antibacterial and aging-resistant granules are blown into a film to obtain an antibacterial and aging-resistant film.

[0044] The antibacterial and aging-resistant film is heat-sealed to form a bag, thus obtaining an antibacterial and aging-resistant shopping bag.

[0045] Optionally, the mixing process is carried out at a rotation speed of 1000~1500 r / min, a temperature of 25~50℃, and a time of 10~30 min.

[0046] Optionally, the melt extrusion granulation is carried out in a twin-screw extruder at a temperature of 140~180℃ and a screw speed of 200~400 r / min.

[0047] Optionally, the blown film treatment is carried out in a blown film unit, with a blown film temperature of 150~190℃, a blow-up ratio of 2.5~3.5, and a traction ratio of 3~5.

[0048] Optionally, the heat-sealing temperature of the heat-sealed bag is 120~160℃, the heat-sealing pressure is 0.2~0.5MPa, and the heat-sealing time is 0.5~2s.

[0049] Thirdly, this application provides the application of the antibacterial and aging-resistant shopping bags described in the aforementioned scheme in the packaging of food, daily necessities, or fresh products.

[0050] The antibacterial and aging-resistant shopping bag provided in this application achieves a balance of antibacterial properties, aging resistance, and mechanical properties through the synergistic effect of epoxy-functionalized PBAT resin, composite antibacterial agent, and aging-resistant masterbatch. Compared with existing technologies, this antibacterial and aging-resistant shopping bag features excellent antibacterial properties, good aging resistance, stable mechanical properties, and good processing performance. Furthermore, the preparation process is simple, and all raw materials are conventional commercially available products, demonstrating good feasibility and industrial application prospects. Detailed Implementation

[0051] The technical solutions in the embodiments of this application will be clearly and completely described below with reference to the embodiments of this application. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application. In addition, it should be understood that the specific implementation methods described herein are only for illustration and explanation of this application and are not intended to limit this application.

[0052] In this application, unless otherwise stated, directional terms such as "upper" and "lower" generally refer to the upper and lower positions of the device in its actual use or operating state; while "inner" and "outer" refer to the outline of the device. Furthermore, in the description of this application, the term "comprising" means "including but not limited to". The terms first, second, third, etc., are used merely as illustrative purposes and do not impose numerical requirements or establish an order.

[0053] In this application, "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural.

[0054] In this application, "at least one" means one or more, and "more than one" means two or more. "One or more", "at least one of the following", or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0055] Various embodiments of this application may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a rigid limitation on the scope of this application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Furthermore, whenever a numerical range is referred to herein, it means including any referenced number (fraction or integer) within the referred range.

[0056] In the first aspect, this application provides an antibacterial and aging-resistant shopping bag, the technical solution of which is as follows:

[0057] An antibacterial and aging-resistant shopping bag, by weight, comprises the following raw materials: 80-95 parts of matrix resin, 5-20 parts of epoxy-functionalized PBAT resin, 0.5-5 parts of composite antibacterial agent, 1-10 parts of aging-resistant masterbatch, 0.5-5 parts of compatibilizer and 0.1-1 parts of lubricant;

[0058] The matrix resin is selected from one or more of PBAT, polylactic acid, polyethylene, or polypropylene;

[0059] The compatibilizer is selected from one or more of the following: ethylene-acrylate copolymer, ethylene-vinyl acetate copolymer, ethylene-glycidyl methacrylate copolymer, and styrene-maleic anhydride copolymer.

[0060] The lubricant is selected from one or more of zinc stearate, calcium stearate, oleamide, or erucamide.

[0061] In this application, the matrix resin serves as the main structural material of the shopping bag. PBAT and polylactic acid are biodegradable resins, providing the shopping bag with excellent biodegradability and meeting environmental protection requirements. Polyethylene and polypropylene are conventional polyolefins with excellent mechanical and processing properties, improving the strength and toughness of the shopping bag. The matrix resin is used in an amount of 80-95 parts to ensure the shopping bag possesses basic mechanical properties and moldability; too low a amount results in insufficient strength, while too high a amount limits the content of other functional components, making it difficult to guarantee antibacterial and aging resistance properties.

[0062] In this application, the compatibilizer improves the compatibility between the matrix resin and the epoxy-functionalized PBAT resin. The compatibilizer contains polar or reactive functional groups, which can form an interfacial bridge between the matrix resin and the epoxy-functionalized PBAT resin, improving blending uniformity and the overall performance of the film. The amount of compatibilizer used is 0.5 to 5 parts; too low a amount results in insufficient compatibilization, while too high a amount may reduce the degradation performance and mechanical strength of the film.

[0063] In this application, the lubricant improves processing performance. The lubricant reduces friction between the melt and the processing equipment, improves melt flowability, reduces material retention in the screw and die, prevents thermal degradation, and facilitates film demolding and opening. The lubricant dosage is 0.1 to 1 part; too low a dosage results in insignificant lubrication, while too high a dosage may cause it to precipitate onto the film surface, affecting the film's appearance and heat-sealing performance.

[0064] In some embodiments, the preparation method of the epoxy-functionalized PBAT resin includes the following steps:

[0065] Adipic acid, terephthalic acid, 1,4-butanediol, tetrabutyl titanate and modified monomers are mixed and then subjected to esterification and polycondensation reactions in sequence. The mixture is then discharged, cooled and granulated to obtain modified poly(adipic acid / butylene terephthalate) copolymer.

[0066] The modified poly(adipate) / butylene terephthalate copolymer, epoxy chain extender and antioxidant are mixed and then subjected to melt reaction extrusion, followed by granulation to obtain the epoxy-functionalized PBAT resin.

[0067] This application uses adipic acid, terephthalic acid, and 1,4-butanediol as basic monomers, and carries out esterification and polycondensation reactions under the catalysis of tetrabutyl titanate. Simultaneously, a modifying monomer is introduced. The modifying monomer is selected from one or more of trimellitic anhydride, pyromellitic anhydride, glycerol, or pentaerythritol, which have multifunctional structures that can form branching points during polycondensation, giving the poly(adipic acid / butylene terephthalate) ester molecular chain a certain branched structure. The introduction of branched structure is beneficial to improving the melt strength and processing stability of the polyester, and provides more reaction sites for subsequent epoxy chain extension reactions. Then, this application uses the modified poly(adipic acid / butylene terephthalate) ester copolymer as a matrix, adds epoxy chain extenders and antioxidants, and performs epoxy chain extension modification through melt reactive extrusion. Epoxy chain extenders are multifunctional epoxy resins whose epoxy groups can react with the carboxyl and hydroxyl groups at the ends of polyester molecular chains, causing chain extension or mild cross-linking of the polyester molecular chains, further increasing molecular weight and melt strength, and improving mechanical properties and aging resistance. Antioxidants protect polyester from thermo-oxidative degradation during melt reactive extrusion.

[0068] In this application, the epoxy-functionalized PBAT resin is used as a functional modifying component in combination with the matrix resin. The epoxy-functionalized PBAT resin is biodegradable and has good compatibility with matrix resins such as PBAT and polylactic acid. Furthermore, its molecular chain contains epoxy functional groups, which can react with the terminal carboxyl and hydroxyl groups in the matrix resin during melt processing, thus playing a role in chain extension and compatibilization, improving melt strength, enhancing interfacial bonding between components, and consequently improving the mechanical properties and aging resistance of the film. The amount of epoxy-functionalized PBAT resin used is 5-20 parts. Too low a dosage results in insignificant compatibilization and chain extension effects; too high a dosage may lead to excessively high melt viscosity, making processing difficult and affecting the flexibility and degradation performance of the film.

[0069] In some embodiments, the mass-to-volume ratio of adipic acid, terephthalic acid, 1,4-butanediol, tetrabutyl titanate, and the modified monomer is 1 g : (1.0~1.4) g : (0.7~1.05) mL : (0.0005~0.005) mL : (0.001~0.01) g, and the modified monomer is selected from one or more of trimellitic anhydride, pyromellitic anhydride, glycerol, or pentaerythritol. In this ratio, adipic acid and terephthalic acid provide a balance between the rigidity and flexibility of the polyester; the amount of 1,4-butanediol ensures complete esterification; the amount of tetrabutyl titanate as a catalyst is moderate to avoid residue affecting product performance; and the modified monomer introduces a branched structure, improving melt strength and subsequent epoxy chain extension efficiency.

[0070] In some embodiments, the esterification reaction is carried out under nitrogen protection at a temperature of 160–220°C for 2–5 hours. Nitrogen protection prevents oxidation and discoloration of the material at high temperatures; the esterification temperature and time ensure sufficient reaction between the carboxyl and hydroxyl groups, laying the foundation for subsequent polycondensation.

[0071] In some embodiments, the polycondensation reaction is carried out at a temperature of 240–270°C, a vacuum level of 10–100 Pa, and a time of 2–6 h. High temperature and high vacuum are beneficial for removing small molecule byproducts, promoting molecular chain growth, and obtaining polyesters with higher molecular weights.

[0072] In some embodiments, the mass ratio of the modified poly(adipate) / butylene terephthalate copolymer, the epoxy chain extender, and the antioxidant is 1:0.005~0.03:0.001~0.005, wherein the epoxy chain extender is selected from one or both of ADR 4368 and ADR4370S. This ratio controls the degree of reaction between the epoxy groups and the polyester end groups, avoiding excessive crosslinking that leads to processing difficulties; the antioxidant effectively inhibits thermo-oxidative degradation during high-temperature melt extrusion.

[0073] In some embodiments, the melt reactive extrusion is carried out in a twin-screw extruder, with a temperature of 160-190°C and a screw speed of 200-300 r / min. The twin-screw extruder provides strong shear mixing, ensuring sufficient contact and reaction between the epoxy chain extender and the polyester end groups; the temperature is higher than the polyester melting point but lower than the decomposition temperature of the epoxy chain extender; and the moderate screw speed ensures sufficient residence time for the material in the barrel to complete the chain extension reaction.

[0074] In some embodiments, the preparation method of the composite antibacterial agent includes the following steps:

[0075] Chitosan, isopropanol aqueous solution and glycidyltrimethylammonium chloride were mixed and subjected to quaternization reaction, then filtered, washed and dried to obtain chitosan quaternary ammonium salt;

[0076] Nano zinc oxide, water, silver nitrate aqueous solution and reducing agent are mixed and a reduction reaction is carried out to obtain silver-loaded nano zinc oxide dispersion;

[0077] The silver-loaded zinc oxide nano-dispersion, chitosan quaternary ammonium salt, and γ-aminopropyltriethoxysilane were mixed and modified, then filtered, washed, dried, and ground to obtain the composite antibacterial agent.

[0078] This application first prepares chitosan quaternary ammonium salt to improve the water solubility and antibacterial activity of chitosan; then prepares silver-loaded zinc oxide nanoparticles to achieve synergistic antibacterial effects of silver and zinc oxide; finally, it modifies the composite antibacterial agent by introducing organic functional groups on the surface of the composite antibacterial agent to improve its compatibility and dispersibility with the resin matrix.

[0079] In this application, the composite antibacterial agent imparts antibacterial function to shopping bags. The composite antibacterial agent is a composite of chitosan quaternary ammonium salt and silver-loaded nano-zinc oxide, and is surface-modified with a silane coupling agent, exhibiting broad antibacterial spectrum, high antibacterial rate, and good migration resistance. The dosage of the composite antibacterial agent is 0.5-5 parts; too low a dosage results in insignificant antibacterial effect; too high a dosage not only increases cost but may also lead to decreased mechanical properties and appearance defects in the film due to inorganic particle aggregation.

[0080] In some embodiments, the mass-to-volume ratio of chitosan, isopropanol aqueous solution, and glycidyltrimethylammonium chloride is 1 g : (10~30) mL : (0.5~2) g, and the volume concentration of the isopropanol aqueous solution is 50%~80%. This ratio ensures that the quaternization reaction proceeds fully, and the concentration of the isopropanol aqueous solution is appropriate, which is beneficial for both the swelling of chitosan and the dissolution of glycidyltrimethylammonium chloride.

[0081] In some embodiments, the quaternization reaction is carried out at a temperature of 60-80°C for 6-12 hours. This temperature and time ensure that glycidyltrimethylammonium chloride reacts fully with chitosan; if the temperature is too low, the reaction rate is slow, and if the temperature is too high, the chitosan may degrade.

[0082] In some embodiments, the first drying temperature is 60-80°C, and the time is 8-12 hours. Drying is carried out under mild conditions to avoid discoloration or decomposition of chitosan quaternary ammonium salts due to high temperatures.

[0083] In some embodiments, the mass-to-volume ratio of the nano-zinc oxide, water, silver nitrate aqueous solution, and reducing agent is 1 g : (15~30) mL : (1~5) mL : (0.1~1) g, the mass concentration of the silver nitrate aqueous solution is 1%~5%, and the reducing agent is selected from one or more of sodium citrate, glucose, or ascorbic acid. This ratio controls the silver loading to be moderate, avoiding excessively large silver particles that affect dispersibility; the reducing agent is a mild reducing agent that reduces silver ions to nano-silver without destroying the nano-zinc oxide structure at a specified temperature.

[0084] In some embodiments, the reduction reaction is carried out at a temperature of 50–80°C for 1–3 hours. This temperature and time ensure complete reduction of silver ions while preventing the growth of silver nanoparticles.

[0085] In some embodiments, the mass-to-volume ratio of the silver-loaded zinc oxide nanoparticle dispersion, chitosan quaternary ammonium salt, and γ-aminopropyltriethoxysilane is 1 mL : (0.02~0.1) g : (0.002~0.02) mL. This ratio ensures that the chitosan quaternary ammonium salt is fully adsorbed and coated on the surface of the silver-loaded zinc oxide nanoparticles, and the amount of γ-aminopropyltriethoxysilane is moderate, which can effectively modify the surface without causing excessive self-condensation to form oligomers.

[0086] In some embodiments, the modification treatment is carried out at a temperature of 50–70°C for 2–4 hours. These conditions are beneficial for the hydrolysis and condensation of the silane coupling agent and its interaction with the chitosan quaternary ammonium salt, thereby completing the surface modification.

[0087] In some embodiments, the second drying temperature is 60~100°C, and the time is 4~12 hours. These drying conditions ensure thorough drying while avoiding thermal decomposition of chitosan quaternary ammonium salt and organic components.

[0088] In some embodiments, the particle size of the milled product is ≤500 nm. Particle size is controlled to ensure good dispersion of the composite antibacterial agent in the resin matrix and to avoid agglomeration.

[0089] In some embodiments, the method for preparing the aging-resistant masterbatch includes the following steps:

[0090] The carrier resin, antioxidant 1010, antioxidant 168, hindered amine light stabilizer 622, ultraviolet absorber UV-326 and polyethylene wax are mixed and stirred to obtain a premix.

[0091] The premixed material is melt-mixed and extruded, and then granulated to obtain the aging-resistant masterbatch.

[0092] This application uses a masterbatch method to pre-disperse various anti-aging additives in the carrier resin, which is beneficial to the uniform dispersion of the additives in the final shopping bag matrix resin and avoids uneven mixing and dust flying caused by density differences when adding additives directly.

[0093] In this application, the aging-resistant masterbatch improves the aging resistance of shopping bags. The aging-resistant masterbatch contains antioxidant 1010, antioxidant 168, hindered amine light stabilizer 622, and ultraviolet absorber UV-326, which can simultaneously inhibit thermo-oxidative aging and photo-oxidative aging, improving the retention rate of mechanical properties of shopping bags under conditions such as light exposure and high temperature. The dosage of the aging-resistant masterbatch is 1-10 parts; too low a dosage results in insufficient aging resistance; too high a dosage, due to the excessively high total content of additives, may affect the transparency, mechanical properties, and processing stability of the film.

[0094] In some embodiments, the carrier resin is selected from one or both of low-density polyethylene and linear low-density polyethylene. These two resins are well-compatible with the polyethylene and polypropylene in the matrix resin, and the processing temperature is moderate, preventing the decomposition of additives during masterbatch preparation.

[0095] In some embodiments, the mass ratio of the carrier resin, antioxidant 1010, antioxidant 168, hindered amine light stabilizer 622, ultraviolet absorber UV-326, and polyethylene wax is 1:0.05~0.15:0.05~0.15:0.05~0.15:0.05~0.15:0.02~0.05. This ratio ensures that the additives reach a high concentration in the masterbatch, facilitating the subsequent achievement of the desired additive content with a smaller amount of masterbatch added. Simultaneously, the polyethylene wax acts as a dispersant, contributing to the uniform dispersion of the additives.

[0096] In some embodiments, the stirring speed is 500~1500 r / min, the temperature is 25~50℃, and the time is 10~30 min. These stirring conditions ensure that the additives and carrier resin particles are fully mixed, and the moderate temperature prevents the additives from decomposing.

[0097] In some embodiments, the melt-mixing extrusion is carried out in a twin-screw extruder at a temperature of 150-180°C and a screw speed of 100-300 r / min. Within this temperature range, the carrier resin is fully melted, and the additives are uniformly dispersed and encapsulated within the carrier resin; the screw speed ensures effective mixing while preventing overheating due to shearing, which could lead to additive decomposition.

[0098] Secondly, this application provides a method for preparing the antibacterial and aging-resistant shopping bag described in the aforementioned scheme, comprising the following steps:

[0099] The matrix resin, epoxy-functionalized PBAT resin, composite antibacterial agent, aging-resistant masterbatch, compatibilizer and lubricant are mixed and then subjected to a mixing treatment to obtain a mixture.

[0100] The mixture is melt-extruded and granulated to obtain antibacterial and aging-resistant granules.

[0101] The antibacterial and aging-resistant granules are blown into a film to obtain an antibacterial and aging-resistant film.

[0102] The antibacterial and aging-resistant film is heat-sealed to form a bag, thus obtaining an antibacterial and aging-resistant shopping bag.

[0103] The preparation method provided in this application first involves uniformly mixing the raw materials through a mixing process, then performing melt extrusion granulation to ensure that the components are fully dispersed and reacted in the molten state, resulting in uniform antibacterial and aging-resistant granules. These granules are then blown into a film, and finally heat-sealed to form shopping bags. The entire process is simple, can be achieved using conventional plastic processing equipment, and is suitable for large-scale production.

[0104] In some embodiments, the mixing process is carried out at a rotation speed of 1000-1500 r / min, a temperature of 25-50°C, and a time of 10-30 min. The mixing process employs a high-speed mixer, mixing at room temperature to 50°C for 10-30 min to ensure sufficient contact between the component particles or powders, and to uniformly disperse the composite antibacterial agent and aging-resistant masterbatch among the matrix resin particles.

[0105] In some embodiments, the melt extrusion granulation is carried out in a twin-screw extruder at a temperature of 140–180°C and a screw speed of 200–400 r / min. This temperature range takes into account the melting characteristics of different matrix resins, while ensuring that the epoxy groups in the epoxy-functionalized PBAT resin undergo chain extension reactions with the end groups of the matrix resin, and avoiding thermal degradation of the biodegradable resin due to excessively high temperatures; the screw speed provides sufficient shear force to ensure thorough mixing of the components, while avoiding excessive shearing that could cause the material temperature to become too high.

[0106] In some embodiments, the blown film processing is carried out in a blown film unit, with a blown film temperature of 150~190°C, a blow-up ratio of 2.5~3.5, and a draw ratio of 3~5. The blown film temperature is adjusted according to the type and formulation of the base resin to ensure stable melt extrusion; the blow-up ratio and draw ratio control the uniformity of film thickness and the balance of longitudinal and transverse mechanical properties.

[0107] In some embodiments, the heat-sealing temperature for the heat-sealed bag is 120~160℃, the heat-sealing pressure is 0.2~0.5MPa, and the heat-sealing time is 0.5~2s. These heat-sealing conditions allow the film to melt and bond at the heat-sealing site, forming a strong bag body, while avoiding excessively high temperatures that could lead to film decomposition or a decrease in heat-sealing strength.

[0108] Thirdly, this application provides the application of the antibacterial and aging-resistant shopping bags described in the aforementioned scheme in the packaging of food, daily necessities, or fresh products.

[0109] The present application will be specifically described below through specific embodiments. The following embodiments are only some embodiments of the present application and are not intended to limit the present application.

[0110] Example 1

[0111] This embodiment provides a method for preparing an antibacterial and aging-resistant shopping bag, including the following steps:

[0112] 70g PBAT, 20g polylactic acid, 10g epoxy-functionalized PBAT resin, 2g composite antibacterial agent, 5g aging-resistant masterbatch, 1.5g ethylene-acrylate copolymer and 0.5g zinc stearate were mixed and stirred at 1200r / min and 30℃ for 15min to obtain the mixture.

[0113] The mixture was added to a twin-screw extruder for melt extrusion granulation. The temperature of each zone of the extruder was 150 / 160 / 170 / 175 / 170℃, and the screw speed was 300r / min, to obtain antibacterial and aging-resistant granules.

[0114] The antibacterial and aging-resistant granules are added to a blown film unit for blown film processing. The blown film temperature is 155 / 165 / 175 / 170℃, the blow-up ratio is 3.0, and the traction ratio is 4, to obtain an antibacterial and aging-resistant film with a thickness of 30μm.

[0115] The antibacterial and aging-resistant film is heat-sealed at a heat-sealing temperature of 140°C, a heat-sealing pressure of 0.4 MPa, and a heat-sealing time of 1 second to produce an antibacterial and aging-resistant shopping bag.

[0116] The preparation method of the epoxy-functionalized PBAT resin includes the following steps:

[0117] 100g adipic acid, 120g terephthalic acid, 80mL 1,4-butanediol, 0.05mL tetrabutyl titanate and 1g trimellitic anhydride were mixed and subjected to esterification at 180℃ for 4h under nitrogen protection, followed by polycondensation at 260℃ and vacuum of 20Pa for 4h. The mixture was discharged, cooled and granulated to obtain modified poly(adipic acid / butylene terephthalate) copolymer.

[0118] 500g of the modified poly(adipate adipate / butylene terephthalate) copolymer, 10g of ADR 4368 and 2g of antioxidant 1010 were mixed and then fed into a twin-screw extruder for melt reaction extrusion. The temperature of each zone was 165 / 170 / 175 / 175 / 170℃ and the screw speed was 250r / min. The mixture was then granulated to obtain the epoxy-functionalized PBAT resin.

[0119] The preparation method of the composite antibacterial agent includes the following steps:

[0120] 20g chitosan, 300mL isopropanol aqueous solution (volume concentration 60%) and 15g glycidyltrimethylammonium chloride were mixed and quaternized at 70℃ and 400r / min for 8h. After filtration, washing and drying at 60℃ for 10h, chitosan quaternary ammonium salt was obtained.

[0121] 10g of nano zinc oxide, 200mL of deionized water, 20mL of silver nitrate aqueous solution (2% by mass) and 2g of sodium citrate were mixed and then subjected to a reduction reaction at 70℃ and 300r / min for 2h to obtain a silver-loaded nano zinc oxide dispersion.

[0122] The silver-loaded zinc oxide nano-dispersion, 8g of chitosan quaternary ammonium salt, and 0.8mL of γ-aminopropyltriethoxysilane were mixed and modified at 60℃ and 300r / min for 3h. After filtration, washing, drying at 80℃ for 8h, and grinding to a particle size ≤500nm, the composite antibacterial agent was obtained.

[0123] The method for preparing the aging-resistant masterbatch includes the following steps:

[0124] 500g of low-density polyethylene, 50g of antioxidant 1010, 50g of antioxidant 168, 50g of hindered amine light stabilizer 622, 50g of ultraviolet absorber UV-326 and 15g of polyethylene wax were mixed and stirred at 1000r / min and 30℃ for 20min to obtain a premix.

[0125] The premixed material is added to a twin-screw extruder for melt mixing and extrusion. The temperature of each zone is 155 / 165 / 170 / 170 / 165℃, and the screw speed is 150r / min. Then, it is granulated to obtain the aging-resistant masterbatch.

[0126] Example 2

[0127] This embodiment provides a method for preparing an antibacterial and aging-resistant shopping bag, including the following steps:

[0128] Mix 80g PBAT, 10g polylactic acid, 10g epoxy-functionalized PBAT resin, 3g composite antibacterial agent, 7g aging-resistant masterbatch, 2g ethylene-glycidyl methacrylate copolymer and 0.8g oleamide, and stir for 10min at 1300r / min and 25℃ to obtain the mixture.

[0129] The mixture was added to a twin-screw extruder for melt extrusion granulation. The temperature of each zone of the extruder was 155 / 165 / 175 / 180 / 175℃, and the screw speed was 350r / min, to obtain antibacterial and aging-resistant granules.

[0130] The antibacterial and aging-resistant granules are added to a blown film unit for blown film processing. The blown film temperature is 160 / 170 / 180 / 175℃, the blow-up ratio is 2.5, and the traction ratio is 5, to obtain an antibacterial and aging-resistant film with a thickness of 25μm.

[0131] The antibacterial and aging-resistant film is heat-sealed at a heat-sealing temperature of 135°C, a heat-sealing pressure of 0.3 MPa, and a heat-sealing time of 1.5 s to produce an antibacterial and aging-resistant shopping bag.

[0132] The preparation method of the epoxy-functionalized PBAT resin includes the following steps:

[0133] 100g adipic acid, 140g terephthalic acid, 100mL 1,4-butanediol, 0.1mL tetrabutyl titanate and 0.5g pyromellitic anhydride were mixed and subjected to esterification at 200℃ for 3h under nitrogen protection, followed by polycondensation at 250℃ and vacuum of 50Pa for 5h. The mixture was discharged, cooled and granulated to obtain modified poly(adipic acid / butylene terephthalate) copolymer.

[0134] 500g of the modified poly(adipate) / butylene terephthalate copolymer, 15g of ADR 4370S and 3g of antioxidant 168 were mixed and then added to a twin-screw extruder for melt reaction extrusion. The temperature of each zone was 170 / 175 / 180 / 180 / 175℃ and the screw speed was 300r / min. The mixture was then granulated to obtain the epoxy-functionalized PBAT resin.

[0135] The preparation method of the composite antibacterial agent includes the following steps:

[0136] 20g chitosan, 400mL isopropanol aqueous solution (volume concentration 50%) and 20g glycidyltrimethylammonium chloride were mixed and quaternized at 60℃ and 500r / min for 12h. After filtration, washing and drying at 70℃ for 12h, chitosan quaternary ammonium salt was obtained.

[0137] 10g of nano zinc oxide, 300mL of deionized water, 30mL of silver nitrate aqueous solution (5% by mass) and 4g of glucose were mixed and then subjected to a reduction reaction at 80℃ and 400r / min for 1h to obtain a silver-loaded nano zinc oxide dispersion.

[0138] The silver-loaded zinc oxide nano-dispersion, 15g of chitosan quaternary ammonium salt, and 1.2mL of γ-aminopropyltriethoxysilane were mixed and modified at 70℃ and 400r / min for 2h. After filtration, washing, drying at 90℃ for 6h, and grinding to a particle size ≤500nm, the composite antibacterial agent was obtained.

[0139] The method for preparing the aging-resistant masterbatch includes the following steps:

[0140] 500g of linear low-density polyethylene, 75g of antioxidant 1010, 75g of antioxidant 168, 75g of hindered amine light stabilizer 622, 75g of ultraviolet absorber UV-326 and 20g of polyethylene wax were mixed and stirred at 1500r / min and 25℃ for 15min to obtain a premix.

[0141] The premixed material is added to a twin-screw extruder for melt mixing and extrusion. The temperature of each zone is 160 / 170 / 175 / 175 / 170℃, the screw speed is 250r / min, and then granulation is performed to obtain the aging-resistant masterbatch.

[0142] Example 3

[0143] This embodiment provides a method for preparing an antibacterial and aging-resistant shopping bag, including the following steps:

[0144] 95g of linear low-density polyethylene, 5g of epoxy-functionalized PBAT resin, 1g of composite antibacterial agent, 3g of aging-resistant masterbatch, 1g of ethylene-vinyl acetate copolymer and 0.3g of calcium stearate were mixed and stirred at 1100r / min and 35℃ for 20min to obtain the mixture.

[0145] The mixture was added to a twin-screw extruder for melt extrusion granulation. The temperature of each zone of the extruder was 160 / 170 / 180 / 180 / 175℃, and the screw speed was 250r / min, to obtain antibacterial and aging-resistant granules.

[0146] The antibacterial and aging-resistant granules were added to a blown film unit for blown film processing. The blown film temperature was 165 / 175 / 185 / 180℃, the blow-up ratio was 3.5, and the traction ratio was 3, resulting in an antibacterial and aging-resistant film with a thickness of 40μm.

[0147] The antibacterial and aging-resistant film is heat-sealed at a heat-sealing temperature of 150°C, a heat-sealing pressure of 0.5 MPa, and a heat-sealing time of 0.5 s to produce an antibacterial and aging-resistant shopping bag.

[0148] The preparation method of the epoxy-functionalized PBAT resin includes the following steps:

[0149] 100g adipic acid, 110g terephthalic acid, 80mL 1,4-butanediol, 0.05mL tetrabutyl titanate and 0.8g glycerol were mixed and subjected to esterification reaction at 170℃ for 5h under nitrogen protection, followed by polycondensation reaction at 270℃ and vacuum degree 10Pa for 3h. The mixture was discharged, cooled and granulated to obtain modified poly(adipic acid / butylene terephthalate) copolymer.

[0150] 500g of the modified poly(adipate adipate / butylene terephthalate) copolymer, 10g of ADR 4368 and 2g of antioxidant 1010 were mixed and then added to a twin-screw extruder for melt reaction extrusion. The temperature of each zone was 165 / 170 / 175 / 175 / 170℃ and the screw speed was 200r / min. The mixture was then granulated to obtain the epoxy-functionalized PBAT resin.

[0151] The preparation method of the composite antibacterial agent includes the following steps:

[0152] 20g chitosan, 250mL isopropanol aqueous solution (70% by volume) and 10g glycidyltrimethylammonium chloride were mixed and quaternized at 80℃ and 300r / min for 6h. After filtration, washing and drying at 80℃ for 8h, chitosan quaternary ammonium salt was obtained.

[0153] 10g of nano zinc oxide, 250mL of deionized water, 15mL of silver nitrate aqueous solution (1% by mass) and 1g of ascorbic acid were mixed and then subjected to a reduction reaction at 50℃ and 300r / min for 3h to obtain a silver-loaded nano zinc oxide dispersion.

[0154] The silver-loaded zinc oxide nano-dispersion, 10g of chitosan quaternary ammonium salt, and 0.5mL of γ-aminopropyltriethoxysilane were mixed and modified at 50℃ and 250r / min for 4h. After filtration, washing, drying at 100℃ for 4h, and grinding to a particle size ≤500nm, the composite antibacterial agent was obtained.

[0155] The method for preparing the aging-resistant masterbatch includes the following steps:

[0156] 500g of low-density polyethylene, 25g of antioxidant 1010, 25g of antioxidant 168, 25g of hindered amine light stabilizer 622, 25g of ultraviolet absorber UV-326 and 10g of polyethylene wax were mixed and stirred at 800r / min and 40℃ for 30min to obtain a premix.

[0157] The premixed material is added to a twin-screw extruder for melt mixing and extrusion. The temperature of each zone is 150 / 160 / 170 / 170 / 165℃, the screw speed is 100r / min, and then granulation is performed to obtain the aging-resistant masterbatch.

[0158] Comparative Example 1

[0159] This comparative example provides a method for preparing an antibacterial and aging-resistant shopping bag, comprising the following steps:

[0160] Mix 70g PBAT, 20g polylactic acid, 10g epoxy-functionalized PBAT resin, 5g aging-resistant masterbatch, 1.5g ethylene-acrylate copolymer and 0.5g zinc stearate, and stir at 1200r / min and 30℃ for 15min to obtain the mixture.

[0161] The mixture was added to a twin-screw extruder for melt extrusion granulation. The temperature of each zone of the extruder was 150 / 160 / 170 / 175 / 170℃, and the screw speed was 300r / min, to obtain antibacterial and aging-resistant granules.

[0162] The antibacterial and aging-resistant granules are added to a blown film unit for blown film processing. The blown film temperature is 155 / 165 / 175 / 170℃, the blow-up ratio is 3.0, and the traction ratio is 4, to obtain an antibacterial and aging-resistant film with a thickness of 30μm.

[0163] The antibacterial and aging-resistant film is heat-sealed at a heat-sealing temperature of 140°C, a heat-sealing pressure of 0.4 MPa, and a heat-sealing time of 1 second to produce an antibacterial and aging-resistant shopping bag.

[0164] The preparation method of the epoxy-functionalized PBAT resin includes the following steps:

[0165] 100g adipic acid, 120g terephthalic acid, 80mL 1,4-butanediol, 0.05mL tetrabutyl titanate and 1g trimellitic anhydride were mixed and subjected to esterification at 180℃ for 4h under nitrogen protection, followed by polycondensation at 260℃ and vacuum of 20Pa for 4h. The mixture was discharged, cooled and granulated to obtain modified poly(adipic acid / butylene terephthalate) copolymer.

[0166] 500g of the modified poly(adipate adipate / butylene terephthalate) copolymer, 10g of ADR 4368 and 2g of antioxidant 1010 were mixed and then fed into a twin-screw extruder for melt reaction extrusion. The temperature of each zone was 165 / 170 / 175 / 175 / 170℃ and the screw speed was 250r / min. The mixture was then granulated to obtain the epoxy-functionalized PBAT resin.

[0167] The method for preparing the aging-resistant masterbatch includes the following steps:

[0168] 500g of low-density polyethylene, 50g of antioxidant 1010, 50g of antioxidant 168, 50g of hindered amine light stabilizer 622, 50g of ultraviolet absorber UV-326 and 15g of polyethylene wax were mixed and stirred at 1000r / min and 30℃ for 20min to obtain a premix.

[0169] The premixed material is added to a twin-screw extruder for melt mixing and extrusion. The temperature of each zone is 155 / 165 / 170 / 170 / 165℃, and the screw speed is 150r / min. Then, it is granulated to obtain the aging-resistant masterbatch.

[0170] Comparative Example 2

[0171] This comparative example provides a method for preparing an antibacterial and aging-resistant shopping bag, comprising the following steps:

[0172] 70g PBAT, 20g polylactic acid, 10g epoxy-functionalized PBAT resin, 2g composite antibacterial agent, 1.5g ethylene-acrylate copolymer and 0.5g zinc stearate were mixed and stirred at 1200r / min and 30℃ for 15min to obtain the mixture.

[0173] The mixture was added to a twin-screw extruder for melt extrusion granulation. The temperature of each zone of the extruder was 150 / 160 / 170 / 175 / 170℃, and the screw speed was 300r / min, to obtain antibacterial and aging-resistant granules.

[0174] The antibacterial and aging-resistant granules are added to a blown film unit for blown film processing. The blown film temperature is 155 / 165 / 175 / 170℃, the blow-up ratio is 3.0, and the traction ratio is 4, to obtain an antibacterial and aging-resistant film with a thickness of 30μm.

[0175] The antibacterial and aging-resistant film is heat-sealed at a heat-sealing temperature of 140°C, a heat-sealing pressure of 0.4 MPa, and a heat-sealing time of 1 second to produce an antibacterial and aging-resistant shopping bag.

[0176] The preparation method of the epoxy-functionalized PBAT resin includes the following steps:

[0177] 100g adipic acid, 120g terephthalic acid, 80mL 1,4-butanediol, 0.05mL tetrabutyl titanate and 1g trimellitic anhydride were mixed and subjected to esterification at 180℃ for 4h under nitrogen protection, followed by polycondensation at 260℃ and vacuum of 20Pa for 4h. The mixture was discharged, cooled and granulated to obtain modified poly(adipic acid / butylene terephthalate) copolymer.

[0178] 500g of the modified poly(adipate adipate / butylene terephthalate) copolymer, 10g of ADR 4368 and 2g of antioxidant 1010 were mixed and then fed into a twin-screw extruder for melt reaction extrusion. The temperature of each zone was 165 / 170 / 175 / 175 / 170℃ and the screw speed was 250r / min. The mixture was then granulated to obtain the epoxy-functionalized PBAT resin.

[0179] The preparation method of the composite antibacterial agent includes the following steps:

[0180] 20g chitosan, 300mL isopropanol aqueous solution (volume concentration 60%) and 15g glycidyltrimethylammonium chloride were mixed and quaternized at 70℃ and 400r / min for 8h. After filtration, washing and drying at 60℃ for 10h, chitosan quaternary ammonium salt was obtained.

[0181] 10g of nano zinc oxide, 200mL of deionized water, 20mL of silver nitrate aqueous solution (2% by mass) and 2g of sodium citrate were mixed and then subjected to a reduction reaction at 70℃ and 300r / min for 2h to obtain a silver-loaded nano zinc oxide dispersion.

[0182] The silver-loaded zinc oxide nano-dispersion, 8g of chitosan quaternary ammonium salt, and 0.8mL of γ-aminopropyltriethoxysilane were mixed and modified at 60℃ and 300r / min for 3h. After filtration, washing, drying at 80℃ for 8h, and grinding to a particle size ≤500nm, the composite antibacterial agent was obtained.

[0183] Comparative Example 3

[0184] This comparative example provides a method for preparing an antibacterial and aging-resistant shopping bag, comprising the following steps:

[0185] Mix 80g PBAT, 20g polylactic acid, 10g epoxy-functionalized PBAT resin, 2g composite antibacterial agent, 5g aging-resistant masterbatch, 1.5g ethylene-acrylate copolymer and 0.5g zinc stearate, and stir at 1200r / min and 30℃ for 15min to obtain the mixture.

[0186] The mixture was added to a twin-screw extruder for melt extrusion granulation. The temperature of each zone of the extruder was 150 / 160 / 170 / 175 / 170℃, and the screw speed was 300r / min, to obtain antibacterial and aging-resistant granules.

[0187] The antibacterial and aging-resistant granules are added to a blown film unit for blown film processing. The blown film temperature is 155 / 165 / 175 / 170℃, the blow-up ratio is 3.0, and the traction ratio is 4, to obtain an antibacterial and aging-resistant film with a thickness of 30μm.

[0188] The antibacterial and aging-resistant film is heat-sealed at a heat-sealing temperature of 140°C, a heat-sealing pressure of 0.4 MPa, and a heat-sealing time of 1 second to produce an antibacterial and aging-resistant shopping bag.

[0189] The preparation method of the composite antibacterial agent includes the following steps:

[0190] 20g chitosan, 300mL isopropanol aqueous solution (volume concentration 60%) and 15g glycidyltrimethylammonium chloride were mixed and quaternized at 70℃ and 400r / min for 8h. After filtration, washing and drying at 60℃ for 10h, chitosan quaternary ammonium salt was obtained.

[0191] 10g of nano zinc oxide, 200mL of deionized water, 20mL of silver nitrate aqueous solution (2% by mass) and 2g of sodium citrate were mixed and then subjected to a reduction reaction at 70℃ and 300r / min for 2h to obtain a silver-loaded nano zinc oxide dispersion.

[0192] The silver-loaded zinc oxide nano-dispersion, 8g of chitosan quaternary ammonium salt, and 0.8mL of γ-aminopropyltriethoxysilane were mixed and modified at 60℃ and 300r / min for 3h. After filtration, washing, drying at 80℃ for 8h, and grinding to a particle size ≤500nm, the composite antibacterial agent was obtained.

[0193] The method for preparing the aging-resistant masterbatch includes the following steps:

[0194] 500g of low-density polyethylene, 50g of antioxidant 1010, 50g of antioxidant 168, 50g of hindered amine light stabilizer 622, 50g of ultraviolet absorber UV-326 and 15g of polyethylene wax were mixed and stirred at 1000r / min and 30℃ for 20min to obtain a premix.

[0195] The premixed material is added to a twin-screw extruder for melt mixing and extrusion. The temperature of each zone is 155 / 165 / 170 / 170 / 165℃, and the screw speed is 150r / min. Then, it is granulated to obtain the aging-resistant masterbatch.

[0196] Comparative Example 4

[0197] This comparative example provides a method for preparing an antibacterial and aging-resistant shopping bag, comprising the following steps:

[0198] Mix 70g PBAT, 20g polylactic acid, 10g epoxy-functionalized PBAT resin, 2g composite antibacterial agent, 5g aging-resistant masterbatch and 0.5g zinc stearate, and stir at 1200r / min and 30℃ for 15min to obtain the mixture.

[0199] The mixture was added to a twin-screw extruder for melt extrusion granulation. The temperature of each zone of the extruder was 150 / 160 / 170 / 175 / 170℃, and the screw speed was 300r / min, to obtain antibacterial and aging-resistant granules.

[0200] The antibacterial and aging-resistant granules are added to a blown film unit for blown film processing. The blown film temperature is 155 / 165 / 175 / 170℃, the blow-up ratio is 3.0, and the traction ratio is 4, to obtain an antibacterial and aging-resistant film with a thickness of 30μm.

[0201] The antibacterial and aging-resistant film is heat-sealed at a heat-sealing temperature of 140°C, a heat-sealing pressure of 0.4 MPa, and a heat-sealing time of 1 second to produce an antibacterial and aging-resistant shopping bag.

[0202] The preparation method of the epoxy-functionalized PBAT resin includes the following steps:

[0203] 100g adipic acid, 120g terephthalic acid, 80mL 1,4-butanediol, 0.05mL tetrabutyl titanate and 1g trimellitic anhydride were mixed and subjected to esterification at 180℃ for 4h under nitrogen protection, followed by polycondensation at 260℃ and vacuum of 20Pa for 4h. The mixture was discharged, cooled and granulated to obtain modified poly(adipic acid / butylene terephthalate) copolymer.

[0204] 500g of the modified poly(adipate adipate / butylene terephthalate) copolymer, 10g of ADR 4368 and 2g of antioxidant 1010 were mixed and then fed into a twin-screw extruder for melt reaction extrusion. The temperature of each zone was 165 / 170 / 175 / 175 / 170℃ and the screw speed was 250r / min. The mixture was then granulated to obtain the epoxy-functionalized PBAT resin.

[0205] The preparation method of the composite antibacterial agent includes the following steps:

[0206] 20g chitosan, 300mL isopropanol aqueous solution (volume concentration 60%) and 15g glycidyltrimethylammonium chloride were mixed and quaternized at 70℃ and 400r / min for 8h. After filtration, washing and drying at 60℃ for 10h, chitosan quaternary ammonium salt was obtained.

[0207] 10g of nano zinc oxide, 200mL of deionized water, 20mL of silver nitrate aqueous solution (2% by mass) and 2g of sodium citrate were mixed and then subjected to a reduction reaction at 70℃ and 300r / min for 2h to obtain a silver-loaded nano zinc oxide dispersion.

[0208] The silver-loaded zinc oxide nano-dispersion, 8g of chitosan quaternary ammonium salt, and 0.8mL of γ-aminopropyltriethoxysilane were mixed and modified at 60℃ and 300r / min for 3h. After filtration, washing, drying at 80℃ for 8h, and grinding to a particle size ≤500nm, the composite antibacterial agent was obtained.

[0209] The method for preparing the aging-resistant masterbatch includes the following steps:

[0210] 500g of low-density polyethylene, 50g of antioxidant 1010, 50g of antioxidant 168, 50g of hindered amine light stabilizer 622, 50g of ultraviolet absorber UV-326 and 15g of polyethylene wax were mixed and stirred at 1000r / min and 30℃ for 20min to obtain a premix.

[0211] The premixed material is added to a twin-screw extruder for melt mixing and extrusion. The temperature of each zone is 155 / 165 / 170 / 170 / 165℃, and the screw speed is 150r / min. Then, it is granulated to obtain the aging-resistant masterbatch.

[0212] The antibacterial and aging-resistant shopping bags prepared in Examples 1-3 and Comparative Examples 1-4 were tested for antibacterial rate, tensile strength, elongation at break, tensile strength retention rate after 500 hours of xenon lamp aging, and heat seal strength. The test results are shown in Table 1. Among them:

[0213] Antibacterial rate test: Cut the film into 50mm×50mm samples, place them in sterile petri dishes, and inoculate them with a concentration of 1×10⁻⁶. 5 0.5 mL of CFU / mL Escherichia coli and Staphylococcus aureus bacterial suspension was used to evenly cover the film surface. The mixture was incubated at 37±1℃ and 90% relative humidity for 24 h. After incubation, the bacterial suspension was washed off with sterile physiological saline, serially diluted, and spread onto plate counting agar. The plates were incubated at 37℃ for 48 h, and the colony count was counted. The antibacterial rate (%) was calculated based on the colony count of the blank control group without the film. Three samples were tested in each group, and the average value was taken.

[0214] Tensile strength and elongation at break tests: The film was cut into dumbbell-shaped specimens (gauge length 25 mm, width 6 mm), clamped on an electronic universal testing machine, and stretched uniformly along the longitudinal axis of the specimen at a tensile speed of 50 mm / min. The stress-strain curve was automatically recorded. The maximum tensile stress at the time of specimen breakage was read as the tensile strength (MPa), and the percentage of the elongation of the gauge length at the time of specimen breakage to the original gauge length was read as the elongation at break (%). Five specimens were tested in each group, and the average value was taken.

[0215] Tensile strength retention test after 500 hours of xenon lamp aging: The film was cut into rectangular samples of 100mm × 50mm and placed in a xenon lamp aging test chamber with an irradiance of 0.51W / m. 2 (Wavelength 340nm), blackboard temperature 65±2℃, relative humidity 50±5%, continuous aging for 500h, after being taken out, placed at room temperature (23±2℃) for 24h to recover naturally, and then the tensile strength after aging was determined according to the above tensile strength test method. The retention rate (%) was taken as the percentage of the tensile strength after aging to the tensile strength before aging. Five samples were tested in each group, and the average value was taken.

[0216] Heat seal strength test: Cut the film into strips of 150mm×15mm. Place the inner surfaces of two strips together and place them between the upper and lower heat seal blades of the heat seal testing machine. The heat seal blade temperature is 140℃, the heat seal pressure is 0.2MPa, and the heat seal time is 1s. After heat sealing, remove the sample and cool it at room temperature (23±2℃) for 1h. Then, clamp the heat-sealed sample on an electronic universal testing machine and perform a T-type peel test at a tensile speed of 200mm / min. Record the maximum peel force during the peeling process. Divide the maximum peel force by the sample width to obtain the heat seal strength (N / 15mm). Test 5 samples in each group and take the average value.

[0217] Table 1

[0218] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 E. coli antibacterial rate / % 99.6 99.7 99.2 0 99.5 99.3 99.5 Staphylococcus aureus antibacterial rate / % 99.4 99.5 99.0 0 99.2 99.1 99.2 Tensile strength / MPa 28.5 30.2 25.8 27.9 28.1 22.5 26.3 Elongation at break / % 460 430 520 450 440 380 420 Tensile strength retention rate after 500 hours of xenon lamp aging / % 87.5 89.2 86.0 85.2 48.3 80.5 84.1 Heat seal strength (N / 15mm) 7.0 7.4 7.8 7.1 7.0 6.2 6.8

[0219] The antibacterial and aging-resistant shopping bags prepared in Examples 1-3 and Comparative Examples 1-4 were tested for right-angle tear strength, puncture strength, light transmittance, and tensile strength retention rate after accelerated UV aging. The test results are shown in Table 2. Wherein:

[0220] Right-angle tear strength test: The film is cut into right-angle tear-type specimens (the specimen size is 100mm×50mm, and a 50mm long cut is made in the center of one end of the specimen along the length direction). The specimen is clamped on an electronic universal testing machine and stretched at a tensile speed of 200mm / min along the longitudinal axis of the specimen. The force-displacement curve during the tearing process is automatically recorded, and the maximum tearing force during the tearing process is read. The right-angle tear strength (kN / m) is obtained by dividing the maximum tearing force by the specimen thickness. Five specimens are tested in each group, and the average value is taken.

[0221] Puncture strength test: The film is cut into circular specimens with a diameter of 80 mm and fixed on the specimen clamp of the puncture test device. A stainless steel puncture needle with a diameter of 1 mm is used to puncture the specimen at a uniform speed of 50 mm / min in a direction perpendicular to the specimen surface. The force-displacement curve is automatically recorded, and the maximum puncture force when the puncture needle punctures the specimen is read as the puncture strength (N). The greater the puncture strength, the better the film's ability to resist puncture by a sharp object. Five specimens are tested in each group, and the average value is taken.

[0222] Transmittance test: Cut the film into 50mm×50mm square samples and place them on the transmittance test bracket of the spectrophotometer. Measure the transmittance of the sample at a wavelength of 550nm. The transmittance (%) is the percentage of transmitted light intensity to incident light intensity. The higher the transmittance, the better the transparency of the film. Test 3 samples in each group and take the average value.

[0223] Tensile strength retention rate test after UV accelerated aging: The film was cut into rectangular samples of 100mm×50mm and placed in a UV accelerated aging test chamber. The UV lamp power was 40W and the wavelength was 300~400nm. The sample was 300mm away from the UV lamp tube. The temperature inside the test chamber was controlled at 40±2℃. The irradiation was carried out for 240h. After removal, the sample was placed at room temperature (23±2℃) for 2h to recover naturally. The tensile strength after irradiation was measured according to the above tensile strength test method. The retention rate (%) was the percentage of the tensile strength after irradiation to the tensile strength before irradiation. The higher the retention rate, the better the UV aging resistance. Five samples were tested in each group and the average value was taken.

[0224] Table 2

[0225] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Right-angle tear strength (kN / m) 38 42 35 37 39 30 33 Puncture intensity / N 4.5 4.8 4.0 4.3 4.5 3.2 3.8 transmittance / % 85 88 80 86 85 82 84 Tensile strength retention rate after UV accelerated aging / % 86 88 84 85 45 78 82

[0226] The technical solutions provided by the embodiments of this application have been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of this application. The description of the above embodiments is only for the purpose of helping to understand the method and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.

Claims

1. An antibacterial and aging-resistant shopping bag, characterized in that, By weight, it includes the following raw materials: The matrix resin consists of 80-95 parts, epoxy-functionalized PBAT resin of 5-20 parts, composite antibacterial agent of 0.5-5 parts, aging-resistant masterbatch of 1-10 parts, compatibilizer of 0.5-5 parts, and lubricant of 0.1-1 parts. The matrix resin is selected from one or more of PBAT, polylactic acid, polyethylene, or polypropylene; The compatibilizer is selected from one or more of the following: ethylene-acrylate copolymer, ethylene-vinyl acetate copolymer, ethylene-glycidyl methacrylate copolymer, and styrene-maleic anhydride copolymer. The lubricant is selected from one or more of zinc stearate, calcium stearate, oleamide, or erucamide.

2. The antibacterial and aging-resistant shopping bag according to claim 1, characterized in that, The preparation method of the epoxy-functionalized PBAT resin includes the following steps: Adipic acid, terephthalic acid, 1,4-butanediol, tetrabutyl titanate and modified monomers are mixed and then subjected to esterification and polycondensation reactions in sequence. The mixture is then discharged, cooled and granulated to obtain modified poly(adipic acid / butylene terephthalate) copolymer. The modified poly(adipate) / butylene terephthalate copolymer, epoxy chain extender and antioxidant are mixed and then subjected to melt reaction extrusion, followed by granulation to obtain the epoxy-functionalized PBAT resin.

3. The antibacterial and aging-resistant shopping bag according to claim 2, characterized in that, The mass-to-volume ratio of adipic acid, terephthalic acid, 1,4-butanediol, tetrabutyl titanate, and the modified monomer is 1 g : (1.0~1.4) g : (0.7~1.05) mL : (0.0005~0.005) mL : (0.001~0.01) g, wherein the modified monomer is selected from one or more of trimellitic anhydride, pyromellitic anhydride, glycerol, or pentaerythritol; and / or The esterification reaction is carried out under nitrogen protection at a temperature of 160–220°C for 2–5 hours; and / or The polycondensation reaction is carried out at a temperature of 240-270℃, a vacuum degree of 10-100 Pa, and a time of 2-6 hours; and / or The mass ratio of the modified poly(adipate) / butylene terephthalate copolymer, epoxy chain extender, and antioxidant is 1:0.005~0.03:0.001~0.005, wherein the epoxy chain extender is selected from one or both of ADR 4368 or ADR 4370S; and / or The melt reactive extrusion is carried out in a twin-screw extruder, with a temperature of 160~190℃ and a screw speed of 200~300r / min.

4. The antibacterial and aging-resistant shopping bag according to claim 1, characterized in that, The preparation method of the composite antibacterial agent includes the following steps: Chitosan, isopropanol aqueous solution and glycidyltrimethylammonium chloride were mixed and subjected to quaternization reaction, then filtered, washed and dried to obtain chitosan quaternary ammonium salt; Nano zinc oxide, water, silver nitrate aqueous solution and reducing agent are mixed and a reduction reaction is carried out to obtain silver-loaded nano zinc oxide dispersion; The silver-loaded zinc oxide nano-dispersion, chitosan quaternary ammonium salt, and γ-aminopropyltriethoxysilane were mixed and modified, then filtered, washed, dried, and ground to obtain the composite antibacterial agent.

5. The antibacterial and aging-resistant shopping bag according to claim 4, characterized in that, The mass-to-volume ratio of chitosan, isopropanol aqueous solution, and glycidyltrimethylammonium chloride is 1 g : (10~30) mL : (0.5~2) g, and the volume concentration of the isopropanol aqueous solution is 50%~80%; and / or The quaternization reaction is carried out at a temperature of 60-80°C for a time of 6-12 hours; and / or The first drying temperature is 60~80℃, and the time is 8~12h; and / or The mass-to-volume ratio of the nano-zinc oxide, water, silver nitrate aqueous solution, and reducing agent is 1 g : (15~30) mL : (1~5) mL : (0.1~1) g, the mass concentration of the silver nitrate aqueous solution is 1%~5%, and the reducing agent is selected from one or more of sodium citrate, glucose, or ascorbic acid; and / or The reduction reaction is carried out at a temperature of 50-80°C for a time of 1-3 hours; and / or The mass-to-volume ratio of the silver-loaded zinc oxide nanoparticle dispersion, chitosan quaternary ammonium salt, and γ-aminopropyltriethoxysilane is 1 mL : (0.02~0.1) g : (0.002~0.02) mL; and / or The modification treatment is performed at a temperature of 50-70°C for 2-4 hours; and / or The second drying temperature is 60~100℃, and the time is 4~12h; and / or The particle size of the ground product is ≤500nm.

6. The antibacterial and aging-resistant shopping bag according to claim 1, characterized in that, The method for preparing the aging-resistant masterbatch includes the following steps: The carrier resin, antioxidant 1010, antioxidant 168, hindered amine light stabilizer 622, ultraviolet absorber UV-326 and polyethylene wax are mixed and stirred to obtain a premix. The premixed material is melt-mixed and extruded, and then granulated to obtain the aging-resistant masterbatch.

7. The antibacterial and aging-resistant shopping bag according to claim 6, characterized in that, The carrier resin is selected from one or both of low-density polyethylene or linear low-density polyethylene; and / or The mass ratio of the carrier resin, antioxidant 1010, antioxidant 168, hindered amine light stabilizer 622, ultraviolet absorber UV-326, and polyethylene wax is 1:0.05~0.15:0.05~0.15:0.05~0.15:0.05~0.15:0.02~0.05; and / or The stirring process is carried out at a speed of 500-1500 r / min, a temperature of 25-50℃, and a time of 10-30 min; and / or The melt-mix extrusion is carried out in a twin-screw extruder at a temperature of 150~180℃ and a screw speed of 100~300r / min.

8. A method for preparing the antibacterial and aging-resistant shopping bag according to any one of claims 1 to 7, characterized in that, Includes the following steps: The matrix resin, epoxy-functionalized PBAT resin, composite antibacterial agent, aging-resistant masterbatch, compatibilizer and lubricant are mixed and then subjected to a mixing treatment to obtain a mixture. The mixture is melt-extruded and granulated to obtain antibacterial and aging-resistant granules. The antibacterial and aging-resistant granules are blown into a film to obtain an antibacterial and aging-resistant film. The antibacterial and aging-resistant film is heat-sealed to form a bag, thus obtaining an antibacterial and aging-resistant shopping bag.

9. The method for preparing the antibacterial and aging-resistant shopping bag according to claim 8, characterized in that, The mixing process is carried out at a rotation speed of 1000~1500 r / min, a temperature of 25~50℃, and a time of 10~30 min; and / or The melt extrusion granulation is carried out in a twin-screw extruder at a temperature of 140~180℃ and a screw speed of 200~400 r / min; and / or The blown film treatment is carried out in a blown film unit, with a blown film temperature of 150~190℃, a blow-up ratio of 2.5~3.5, and a draw ratio of 3~5; and / or The heat-sealing temperature for the heat-sealed bag is 120~160℃, the heat-sealing pressure is 0.2~0.5MPa, and the heat-sealing time is 0.5~2s.

10. The use of the antibacterial and aging-resistant shopping bag according to any one of claims 1 to 7 in the packaging of food, daily necessities or fresh products.